Preparation method of flame-retardant, high-refraction and melt-drop-resistant polyurethane coating

By introducing carbon-forming agents and high-refractive materials into aqueous polyurethane coatings, a dense carbon layer and a high-refractive layer are formed, the flame retardancy, droplet properties and refractive index of aqueous polyurethane coatings are solved, and the comprehensive performance improvement of high oxygen index, low melt droplets and high refractive are achieved.

CN119842310AActive Publication Date: 2025-04-18YANTAI UNIV

Patent Information

Application Number
CN202510333567.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-04-18
Estimated Expiration
2045-03-20

AI Technical Summary

Technical Problem

When burning, water-based polyurethane coatings have low oxygen index, large smoke release, and are prone to melt droplets, causing rapid spread of fire and uneven volume shrinkage during film formation, making it difficult to meet the requirements of high refractive and heat resistance.

Method used

Polypropylene glycol and polytetrahydrofuran ether glycol are used as polyols to react with isophorone diisocyanate and hexamethylene diisocyanate to form a prepolymer, add the carbon-forming agent N-vinyl carbazole and DOPO, chain extender 2,2-dihydroxybutyric acid and amino carbon nanotubes, introduce the high refractive material 2,5-dimethylthio-1,4-dithiane, neutralizing agent triethylamine and water emulsification to form a dense carbon layer and a high refractive layer, improving flame retardant and droplet resistance.

Benefits of technology

It significantly improves the oxygen index of water-based polyurethane coatings, inhibits the droplet phenomenon, reduces combustion rate and smoke generation rate, enhances heat resistance and refractive index, reduces film cooling and shrinkage, and improves the stability and safety of polyurethane.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of a flame-retardant, high-refraction and melt-drop-resistant water-based polyurethane coating, which comprises the following steps: adding dihydric alcohol, isocyanate and dibutyltin dilaurate into a 500mL flask, heating to 70-85 DEG C, and stirring to react for 1-2 hours to obtain a polyurethane prepolymer; adding a charring agent into the polyurethane prepolymer, and continuously reacting for 1-2 hours; cooling to 60 DEG C, and then adding 2, 2-dimethylolbutyric acid and amino carbon nanotubes to react for 0.5-1 hour; adding a high-refraction material, reacting at 65-70 DEG C for 1-2 hours, cooling to 40 DEG C, adding triethylamine, and reacting for 0.5-1 hour; the preparation method comprises the following steps: adding deionized water, adding an ammonium polyphosphate solution at a rotating speed of 2000r / min, and carrying out high-speed shearing emulsification for 0.5-1h to obtain the flame-retardant, high-refraction and melt-drop-resistant polyurethane coating which has the advantages of high flame retardance, high refractive index and no melt drop.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a waterborne polyurethane coating, in particular to a method for preparing a flame-retardant, high-refractive and drip-resistant waterborne polyurethane coating. Background Art

[0002] Waterborne polyurethane (WPU) is widely used in the fields of finishing agents, coatings and adhesives due to its good mechanical properties, environmental protection, pollution-free and easy modification. It is used in various industries such as wood products, automobiles, aircraft, machinery, electrical appliances, instruments and meters, plastics, leather, paper, fabrics, petrochemicals, etc. However, as a high-performance polymer material, WPU has a low limiting oxygen index (LOI), usually around 18%, which means that it is very easy to ignite in the air. And once ignited, the fire will spread rapidly, producing a large amount of smoke and toxic gases, posing a great threat to human health. In addition, due to its fast burning speed and accompanied by high-temperature molten droplets, it is very easy to cause secondary fires, causing more serious harm. Therefore, improving the flame retardancy of WPU is an important research direction in the field of WPU.

[0003] According to the different ways of introducing flame retardants into WPU, they can be divided into additive flame retardants and reactive flame retardants. Compared with additive flame retardants, reactive flame retardants can overcome the problems of poor solubility with WPU, easy migration, large dosage, and reduced mechanical properties of WPU, and have a better flame retardant effect. So far, a large number of studies on reactive flame retardant WPU have been reported, including nitrogen, phosphorus, and silicon compounds. Among them, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) is a new flame retardant intermediate. Because of its cyclic O=PO bond, it has higher thermal stability and chemical stability than general uncirculated organophosphorus flame retardants. Therefore, it has received widespread attention. Based on the addition reaction of DOPO's PH bond with the C=C, C=O, and C=N double bonds of the substrate under heating conditions, researchers have designed and synthesized many DOPO derivative flame retardants.

[0004] Yaofa Luo et al. synthesized PNB organic flame retardant using 4-formylphenylboronic acid, 4-aminothiophenol, and 9,10-dihydro-9-oxa-10-phosphoanthracene-10-oxide (DOPO) as raw materials, and then introduced PNB flame retardant into the molecular chain of hydroxy-terminated polybutadiene-acrylonitrile (HTBN) to successfully prepare macromolecular flame retardant APFBH for the preparation of flame-retardant waterborne polyurethane. When APFBH is 7.5%, a LOI value of 29.8% and a UL-94 V-0 grade can be achieved, greatly improving the droplet phenomenon. With the increase of APFBH content, the tensile strength and elongation at break of FR-WPU first increase and then decrease. The flame retardant properties of WPU are improved, but the quality of carbon layer formation is still not ideal, the LOI value also has room for improvement, and the mechanical properties of polyurethane are reduced.

[0005] The invention patent CN119320596A of Duan Baorong et al. is a method for preparing a flame-retardant, washable, and drip-resistant water-based polyurethane coating, which aims to solve the problem of low heat release, drip-resistant, washable, and degradable polyurethane coatings in PCB processing. In view of the drawbacks of existing washable coatings, the carbonizing agent and polyhydroxy single-walled nanotube prepolymerization reaction, porous carbon layer modifiers and glucose modifier chain extension, and high carbonizing agent modification are used to solve the problem of polyurethane having no dripping and low heat release when heated, thereby improving the flame retardancy of polyurethane; the water washability of glucose modifiers, the degradability of polycaprolactone diol and glucose are used to improve the degradability and water washability of polyurethane. The oxygen index of this invention is low, and the refractive resistance of polyurethane is not involved.

[0006] Invention patent CN113956777B of Duan Baorong et al. uses polypropylene glycol and polytetramethylene glycol as polyols, modified HGB-NCO as isocyanate, 2,2-dithiodiethanol chain extender and intumescent flame retardant as monomer raw materials, and synthesizes HGB-waterborne polyurethane prepolymer through prepolymerization reaction. Then add a neutralizer to neutralize the prepolymer, and finally add an equal proportion of water for emulsification to finally obtain HGB-WPU. Among them, hollow glass microspheres are a new type of hollow material with the advantages of low thermal conductivity and non-flammability. Moreover, hollow glass microspheres are mainly composed of soda lime borosilicate, which is a non-combustible substance itself. It is added to WPU (waterborne polyurethane) to reduce its volume fraction and indirectly act as a flame retardant. In addition, due to the advantages of light weight and heat insulation of hollow glass microbeads, they can migrate from the inside of the coating to the surface of the sample when HGB-WPU burns, thereby isolating the fire source and playing a good flame retardant role, enhancing the stability of the carbon layer and reducing the droplet phenomenon. Due to the large particle size of HGB, the stability of polyurethane used in polyurethane is poor, the storage period of the obtained polyurethane coating is short, and its industrialization is limited.

[0007] In recent years, intelligent optoelectronic devices such as flexible displays and micro-sensors have developed rapidly, and high-performance optical materials are the basis for realizing the functions of advanced optical devices. Although traditional inorganic optical materials have advantages such as high strength, high refractive index, and low dispersion, their disadvantages of high brittleness, heavy weight, and high processing difficulty limit their development in advanced optical devices. Organic optical materials have become the preferred materials for advanced optical devices due to their adjustable performance, light texture, easy processing, and low resistance. They are used in high-performance substrates, packaging materials for light-emitting diodes (LEDs), and microlenses for charge-coupled devices (CCDs) or complementary metal oxide semiconductor (CMOS) image sensors. However, compared with inorganic optical materials, the molecular structure characteristics of organic optical materials result in poor thermal stability and low refractive index. Among them, the refractive index is the most critical parameter of optical organic materials. The disadvantage of low refractive index hinders the progress of high-precision optical devices.

[0008] Currently, the use of polyurethane in these fields requires good heat resistance and flame retardancy as well as good refractive resistance, but there is almost no research on the refractive index of water-based polyurethane.

[0009] Invention patent CN111303478A relates to naked-eye 3D display screen materials and preparation methods thereof, the method comprising the following steps: providing a polymer solution in which a base material is dissolved in a volatile solvent, wherein the base material is an optically transparent material, and the volatile solvent is immiscible with water; casting the polymer solution on an optically transparent substrate in a constant temperature and humidity sealed container, and promoting the nucleation and growth of water droplets on the surface of the polymer solution through the volatilization of the volatile solvent; then allowing the optically transparent substrate cast with the polymer solution to stand in a constant temperature and humidity sealed container, and waiting for the volatile solvent and water droplets to completely volatilize, and forming a microstructure of spherical pits left by water droplets on the surface of the base material, thereby obtaining a naked-eye 3D display screen material, the resin material used is mainly self-polystyrene-butadiene-styrene block copolymer, polycarbonate, polyethyleneimine or polymethyl methacrylate, and its light transmittance is less than 95%, and the flame retardancy and droplet resistance in terms of heat resistance are not emphasized, and it is not used in polyurethane.

[0010] In summary, polyurethane is widely used, but it still has problems such as low oxygen index, large smoke release, and improper control, and there are still some molten droplets. For specific fields that require high refractive index, there is also volume shrinkage of the polyurethane film during the cooling process of the film forming process. Polyurethane still does not meet the use requirements, so high refractive index is needed to assist heat-resistant polyurethane materials. Summary of the invention

[0011] Aiming at the low oxygen index of polyurethane, large smoke release, improper use, partial droplets, and partial volume shrinkage of polyurethane during film forming and cooling process, the present invention uses polypropylene glycol and polytetramethylene ether glycol as polyols, isophorone diisocyanate and hexamethylene diisocyanate as isocyanates, and synthesizes prepolymer under the condition of dibutyltin dilaurate as catalyst; then adds a carbonizing agent modified by N-vinyl carbazole for chain extension, the carbonizing agent can inhibit the generation of droplets by the combustion of polyurethane, and the formed poly N-vinyl carbazole has strong rigidity, and the polyurethane film has small shrinkage when cooled; then uses a chain extender 2,2-dihydroxybutyric acid (DMBA) and amino carbon nanotubes for a second chain extension , amino carbon nanotubes with a dense carbon layer under heating conditions and good thermal conductivity are introduced into the polyurethane chain segment to make up for the lack of strong carbon density in the first chain extension, and then high-refractive material and 2,5-dimethylmercapto-1,4-dithiane are introduced for the third chain extension, wherein the high-refractive material is a high-refractive compound doped with nitrogen, phosphorus and sulfur containing an imino group, and sulfur is introduced into 2,5-dimethylmercapto-1,4-dithiane to make up for the insufficient refractive index of the high-refractive material, while avoiding yellowing inside the polyurethane and improving the yellowing resistance of the polyurethane, triethylamine is used to neutralize the prepolymer, and water is used for emulsification, and finally a flame-retardant, high-refractive, and drip-resistant water-based polyurethane coating is obtained.

[0012] The preparation method of the flame retardant, high refractive, and drip resistant water-based polyurethane coating comprises the following steps: (1) Take 30-32 g of diol, 14.92 g of isocyanate and 0.2-0.3 g of dibutyltin dilaurate, add them into a 500 mL three-necked flask, raise the temperature to 70-85 °C, rotate at 300-500 r / min under nitrogen protection, and stir for 1-2 h to obtain a polyurethane prepolymer; (2) Add 4.2-8.4 g of carbonizing agent to the polyurethane prepolymer and continue to react at 70-80 °C for 1-2 h; cool to 60 °C, add 0.73-0.89 g of 2,2-dihydroxymethylbutyric acid and 2.4-2.6 g of amino carbon nanotubes, and react at 60-65 °C for 1-2 h; add 1.64-2.46 g of high refractive material and 1.06-1.21 g of 2,5-dimethylmercapto-1,4-dithiane, and react at 65-70 °C for 1-2 h; cool to 40 °C, add 2.1 g of triethylamine, and react for 0.5-1 h; cool to room temperature, add 50-80 mL of deionized water, and emulsify at 2000 r / min for 0.5-1.5 h. h, then add 13.15 g of ammonium polyphosphate solution dissolved in 10 g of water and 0.2-0.3 g of organic and inorganic negative heat materials, and emulsify at a high speed of 1000-2000 r / min for 0.5-1 h. When the foam disappears, a flame-retardant, high-refractive, and drip-resistant water-based polyurethane coating is obtained.

[0013] The diol is any one of polypropylene glycol and polytetramethylene glycol or a mixture of the two in any ratio; The isocyanate is any one of isophorone diisocyanate and hexamethylene diisocyanate or a mixture of the two in any ratio; The number average molecular weight of polypropylene glycol and polytetramethylene glycol is 2000 g / mol.

[0014] Preparation method of flame-retardant, high-refractive, and drip-resistant water-based polyurethane coating, and preparation method of the carbon-forming agent: (1) Add 24.4 g of p-hydroxybenzaldehyde PHBA into a beaker, stir and dissolve it with 150-200 mL of ethanol, transfer it into a 500 mL three-necked flask, and heat it to 60-70 °C under nitrogen protection. The stirring speed is 300-500 r / min. Dilute 6-6.2 g of ethylenediamine with 50 mL of ethanol and add it dropwise to the p-hydroxybenzaldehyde solution for 30-50 min. Continue to react for 2-2.5 h. Cool it to room temperature, wash it with ethanol 2-3 times, and vacuum dry it at 60-70 °C for 12-24 h to obtain a light yellow carbon-forming intermediate powder PHE. (2) Put 26.8 g of PHE described in step (1) in a beaker, add 150-200 mL of ethanol as a solvent, pour into a 500 mL three-necked flask, and heat to 70-80° C. under nitrogen protection. Add 2-43.2 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO4 and 0.7-1.2 g of N-vinylcarbazole, stir at a speed of 200-300 r / min, and react for 3-6 hours. Stop heating, cool to room temperature, wash with ethanol 2-3 times, and recrystallize with methanol 2-3 times to obtain a white carbon-forming agent powder PHED, and dry in a vacuum at 60-70° C. for 24 hours to obtain the carbon-forming agent.

[0015] The preparation method of amino carbon nanotubes is as follows: 0.6-0.7 g of carbon nanotubes were subjected to ultrasonic dispersion treatment for 2-3 h in the presence of 80-90 mL of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3: 1. After ultrasonication, the mixed solution was diluted with 80-100 mL of water, the acid solution was filtered with a vacuum pump, washed with deionized water until neutral, and dried at 105° C. overnight to obtain carboxylated carbon nanotubes; 3.00-3.25 g of phosphorus trichloride was dissolved in DMF solution, 0.205 g of carboxylated carbon nanotubes and 4.3 g of bis(2-ethylhexanoic acid)hydroxyaluminum were added, and the mixture was reacted at 50-60° C. for 30-60 min, then placed in a constant temperature oil bath at 70-80° C., 7.2-7.5 g of acrylamide was added, and the mixture was reacted for 24-48 h, and washed with 10 mL of DMF and 30 mL of toluene in sequence, filtered, and dried at 105° C. in vacuum overnight to obtain amino carbon nanotubes.

[0016] Preparation method of high refractive material: (1) Add 10.7 g of 2-carboxyethylphenylphosphorous acid into a 250 mL three-necked flask, add 50-60 mL of thionyl chloride, install a tail gas saturated sodium hydroxide solution treatment device, heat to 70-80 ° C, slowly pass nitrogen, stir and react for 2-3 hours, cool to room temperature, and remove thionyl chloride by rotary evaporation to obtain an oily liquid to obtain phosphorus impurities; (2) Under nitrogen protection, 54-57 g of 4-aminothiophenol is dissolved in 200 mL of 1,3-dimethyl-2-imidazolidinone, and 40-42 g of sodium carbonate and 150 mL of toluene are added and stirred. The temperature is raised to 120-140° C. to collect evaporated toluene, and the temperature is lowered to 110-120° C. after the toluene is removed. Then, a mixed solution of 29 g of 2,5-dichlorothiophene and 50-60 mL of DMI is added to the reaction flask and reacted for 6-8 h. Then, 21.5-22 g of the phosphorus impurity in step (1) is added and reacted at 90-110° C. for 1-2 h. Then, the obtained product is poured into 1 L of ice water and allowed to stand until the product solidifies into a solid. Then, the solid is collected by suction filtration and washed with a large amount of deionized water to finally obtain a pale yellow solid as a crude product. The crude product can be recrystallized from anhydrous ethanol and mixed with 1.3 g of thiadiazole to obtain a pure white needle-shaped solid to obtain a high refractive material.

[0017] The degree of polymerization of the ammonium polyphosphate is less than 20.

[0018] Preparation method of organic and inorganic negative heat materials: 1.26 g of 10% by mass oxalic acid aqueous solution was dripped dropwise into 20 mL of a mixed aqueous solution of 0.2-0.3 g of cadmium nitrate tetrahydrate, 0.18-0.22 g of zirconium oxynitrate hydrate, and 0.14-0.18 g of aluminum nitrate, and 10-15 mL of concentrated nitric acid was added dropwise thereto, and stirred at room temperature at a speed of 800-1000 rpm for 30-60 min to obtain a white mixed solution, which was washed with deionized water and ethanol several times, and dried at 110-140° C. to obtain a white product, and the obtained particles were crushed into particles less than 10 μm to obtain an organic-inorganic negative heat material.

[0019] The advantages of the present invention are: (1) The present invention uses p-hydroxybenzaldehyde and ethylenediamine as raw materials for reaction, uses ethanol as a reaction solvent to increase the reaction rate, forms an intermediate PHE, and then adds 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) to react with the intermediate PHE to form a flame retardant PHED with high carbonization and two hydroxyl functional groups (reacting with waterborne polyurethane isocyanate groups). The cost of raw materials used in the preparation process of the flame retardant is relatively low; the flame retardant PHED contains phosphorus and nitrogen elements, and phosphorus compounds can be decomposed into phosphoric acid, metaphosphoric acid and polyphosphoric acid at high temperatures, and these compounds can be used as inhibitors in combustion reactions. Phosphoric acid, metaphosphoric acid and polyphosphoric acid can react with materials and can be wrapped on the surface of materials to form a barrier that is difficult to burn, effectively inhibiting the combustion reaction. Secondly, phosphorus compounds need to absorb heat to decompose during combustion, which will reduce the temperature of the combustion reaction, thereby slowing down the speed of the combustion reaction. The nitrogen compounds in the flame retardant decompose at high temperatures to produce nitrogen compounds, such as hydrogen (N2), ammonia (NH3), nitrogen trioxide (NO3), etc. These gases will form a stable protective layer on the surface of the material, dilute the oxygen concentration, prevent the flame and heat from continuing to burn and conduct to the material, and play a flame retardant role. At the same time, these gases can react with the free radicals produced by combustion to form stable compounds, blocking the chain reaction, thereby slowing down the combustion process and inhibiting the spread of the flame. At the same time, the flame retardant nitrogen compounds will absorb a large amount of heat during the decomposition process, thereby reducing the surface temperature of the material and slowing down the combustion rate. This endothermic effect can prevent the flame from propagating into the material and protect the polyurethane material; N-vinyl carbazole in the carbonizing agent polymerizes with the double bond of DOPO, and introduces nitrogen-condensed ring compounds into the carbonizing agent, which improves the heat resistance of polyurethane and greatly reduces the area shrinkage rate of the polyurethane film when it is cooled.

[0020] (2) Since traditional carbon nanotubes are thin and light, they can cause droplets to fall when used in waterborne polyurethane, but their oxygen index is not significantly increased. Therefore, it is necessary to improve the density of the combustion products so that the carbon layer can bear the heat of combustion in an environment with high oxygen concentration. The carbon nanotubes are oxidized under the strong acid conditions of sulfuric acid and nitric acid to produce a large number of hydroxyl and carboxyl groups on the surface of the carbon nanotubes. Phosphorus trichloride is used to react with some hydroxyl and carboxyl groups in carboxylated carbon nanotubes and bis(2-ethylhexanoic acid) hydroxyaluminum to introduce acyl chloride bonds into the system, and then react with acrylamide to introduce imine groups into the system, which can react with some isocyanate groups in the polyurethane chain extension stage and introduce the carbonized part into the polyurethane system. In this reaction, phosphorus trichloride plays a role in enhancing the acidity under heating environment, thereby enhancing the density of the carbon layer formed by the carbon nanotubes, while bis(2-ethylhexanoic acid) hydroxyaluminum plays a role in enhancing the density of the carbon layer of the carbon nanotubes. In addition, the aluminum oxide produced by its thermal combustion has good thermal conductivity, which improves the flame retardancy of the carbon nanotubes. (3) Using polypropylene glycol and polytetramethylene glycol as polyols, isophorone diisocyanate and hexamethylene diisocyanate as isocyanates, and using dibutyltin dilaurate as a catalyst to synthesize a prepolymer; then adding a carbonizing agent to extend the chain, which can inhibit the generation of molten droplets by the combustion of polyurethane; then using a chain extender 2,2-dihydroxybutyric acid (DMBA) and amino carbon nanotubes to extend the chain for the second time, introducing amino carbon nanotubes with a dense carbon layer and good thermal conductivity under heating conditions into the polyurethane chain segment to make up for the first chain extension. In order to overcome the shortcomings of low carbonization and compactness, a high-refractive material and 2,5-dimethylmercapto-1,4-dithiane are introduced for a third chain extension. The high-refractive material is a high-refractive compound doped with nitrogen, phosphorus and sulfur containing an imino group. Sulfur is introduced into 2,5-dimethylmercapto-1,4-dithiane to make up for the insufficient refractive index of the high-refractive material, and yellowing inside the polyurethane is avoided, thereby improving the yellowing resistance of the polyurethane. The prepolymer is neutralized by a neutralizing agent, triethylamine, and finally water is added for emulsification, thereby finally obtaining a flame-retardant, high-refractive, and drip-resistant water-based polyurethane coating. (4) The use of a carbonizing agent can solve the problem of molten droplets generated when the polyurethane film is burned. The oxygen index of the obtained polyurethane film is around 28%. When a carbonizing agent is used in conjunction with APP for flame retardancy, the oxygen index of the obtained polyurethane film can exceed 32%, but it will cause the polyurethane film to burn and produce molten droplets. Therefore, amino carbon nanotubes are distributed in the polyurethane chain segments to enhance the distribution of the dense carbon layer. When the polyurethane burns, a dense carbon layer is distributed in the amorphous polyurethane, and the dripping of the burning molten droplets is suppressed; (5) The present invention reacts the hydroxyl group in 2-carboxyethylphenylphosphorous acid with thionyl chloride to replace the carboxyl hydroxyl group and phosphorus hydroxyl group of 2-carboxyethylphenylphosphorous acid, thereby increasing the phosphorus content in the system and improving the refractive index of the polyurethane; (6) The chlorine atom on 2,5-dichlorothiophene is easy to leave to generate carbon cations and chloride ions, while sodium carbonate provides an alkaline environment to convert the thiol group (Ar-SH) on 4-aminothiophenol into a Lewis base (Ar-S-). The Lewis base acts as a nucleophilic reagent to attack the carbon cation to generate a thioether bond, and the generated HCl is immediately captured by the alkaline environment and converted into a chloride salt, which promotes the nucleophilic substitution reaction. The introduction of atoms or groups with high molar refractive index such as sulfur atoms can improve the refractive index of the material, and the amino group of the product reacts with the acyl chloride and phosphorus chloride of the phosphorus doped substance, and is mixed with thiadiazole to form a high refractive index compound containing nitrogen, phosphorus and sulfur doped with an imino group. The high refractive index material is introduced into the polyurethane chain segment. Due to the ring rigidity of 2-carboxyethylphenylphosphorous acid, 2,5-dichlorothiophene and 4-aminothiophenol, the refractive index of the polyurethane is improved, and the shrinkage rate of the polyurethane film during heating and cooling is reduced.

[0021] (7) The multi-metal organic framework material connected by small molecule oxalic acid ligands has a synergistic effect with cadmium, zirconium and aluminum. Due to the torsion and deformation of cadmium oxygen, zirconium oxygen and aluminum oxygen in the inorganic layer, negative thermal expansion is generated in the inorganic layer, which synergizes with the positive thermal expansion in the organic layer, so that the obtained material has negative thermal expansion in the two-dimensional plane, so that it does not expand too much under the high temperature conditions of polyurethane film formation, and the expansion recovery of the suppressed part is restored when used at room temperature. DETAILED DESCRIPTION

[0022] The present invention is further described below with reference to examples.

[0023] The chemical materials of unspecified manufacturers involved in the embodiments of the present invention can be replaced with similar products of Shanghai MacLean Biochemical Co., Ltd. Embodiment 1

[0024] The preparation method of the flame retardant, high refractive, and drip resistant water-based polyurethane coating comprises the following steps: (1) 30 g of polypropylene glycol (number average molecular weight: 2000 g / mol), 14.92 g of isophorone diisocyanate and 0.2 g of dibutyltin dilaurate were added to a 500 mL three-necked flask. Under nitrogen protection, the temperature was raised to 70 °C and the speed was 300 r / min for stirring and reacting for 1 h to obtain a polyurethane prepolymer. (2) Add 4.2 g of carbonizing agent to the polyurethane prepolymer and continue to react at 70°C for 1 h; cool to 60°C, add 0.73 g of 2,2-dihydroxymethylbutyric acid and 2.4 g of amino carbon nanotubes, and react at 60°C for 1 h; add 1.64 g of high refractive material and 1.06 g of 2,5-dimethylmercapto-1,4-dithiane, and react at 65°C for 1 h; cool to 40°C, add 2.1 g of triethylamine and react for 0.5 h; cool to room temperature, add 50 mL of deionized water, and emulsify at a speed of 2000 r / min for 0.5 h; then add 13.15 g of ammonium polyphosphate (the degree of polymerization of ammonium polyphosphate is less than 20) solution dissolved in 10 g of water and 0.2 g of organic and inorganic negative heat material, and emulsify at a speed of 1000 r / min for 0.5 h. After the foam disappears, a flame retardant, high refractive, and drip-resistant water-based polyurethane coating is obtained.

[0025] The preparation method of the carbon-forming agent: (1) Add 24.4 g of p-hydroxybenzaldehyde PHBA into a beaker, stir and dissolve with 150 mL of ethanol, transfer to a 500 mL three-necked flask, and heat to 60 °C under nitrogen protection with a stirring speed of 300 r / min. Dilute 6 g of ethylenediamine with 50 mL of ethanol and add dropwise to the p-hydroxybenzaldehyde solution for 30 min. Continue the reaction for 2 h. Cool to room temperature, filter and obtain a pale yellow crude carbon-forming intermediate. Wash with ethanol twice and vacuum dry at 60 °C for 12 h to obtain a pale yellow carbon-forming intermediate powder PHE. (2) Put 26.8 g of PHE described in step (1) in a beaker, add 150 mL of ethanol as solvent, pour into a 500 mL three-necked flask, and heat to 70°C under nitrogen protection. Add 2 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO4 and 0.7 g of N-vinylcarbazole. The speed is 200 r / min and stirred for reaction for 3 h. Stop heating, cool to room temperature, wash with ethanol twice, and recrystallize with methanol several times to obtain a white carbon-forming agent powder PHED. Dry in vacuum at 60°C for 24 h to obtain the carbon-forming agent.

[0026] The preparation method of amino carbon nanotubes is as follows: 0.6 g of carbon nanotubes were subjected to ultrasonic dispersion treatment for 2 h in the presence of 80 mL of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3: 1. After ultrasonication, the mixed solution was diluted with 80 mL of water, the acid solution was filtered with a vacuum pump, washed with deionized water until neutral, and dried at 105° C. overnight to obtain carboxylated carbon nanotubes; 3.00 g of phosphorus trichloride was dissolved in 10 mL of DMF solution, 0.205 g of carboxylated carbon nanotubes and 4.3 g of bis(2-ethylhexanoic acid)hydroxyaluminum were added, reacted at 50° C. for 30 min, then placed in a constant temperature oil bath at 70° C., 7.2 g of acrylamide was added and reacted for 24 h, washed with 10 mL of DMF and 30 mL of toluene in turn, filtered, and dried at 105° C. in vacuum overnight to obtain amino carbon nanotubes.

[0027] Preparation method of high refractive material: (1) Add 10.7 g of 2-carboxyethylphenylphosphite into a 250 mL three-necked flask, add 50 mL of thionyl chloride, install a tail gas saturated sodium hydroxide solution treatment device, add a magnet, raise the temperature to 70 ° C, slowly pass nitrogen, react for 2 hours, cool to room temperature, and remove thionyl chloride by rotary evaporation to obtain an oily liquid, which is the phosphorus impurity; (2) Under nitrogen protection, 54 g of 4-aminobenzenethiol was dissolved in 200 mL of 1,3-dimethyl-2-imidazolidinone (DMI), and 40 g of sodium carbonate and 150 mL of toluene were added and stirred. The temperature was raised to 120°C to collect the evaporated toluene, and the temperature was lowered to 110°C after the toluene was removed. Then, a mixed solution of 29 g of 2,5-dichlorothiophene and 50 mL of DMI was added to the reaction bottle and reacted for 6 h. Then, 21.5 g of the phosphorus dopant in step (1) was added and reacted at 90°C for 1 h. The obtained product was poured into 1 L of ice water and allowed to stand until the product solidified into a solid. The solid was collected by suction filtration and washed with a large amount of deionized water to finally obtain a pale yellow solid as a crude product. The crude product can be recrystallized from anhydrous ethanol to obtain a pure white needle-shaped solid, which is then mixed with 1.3 g of thiadiazole to obtain a high refractive material.

[0028] Preparation method of organic and inorganic negative heat materials: 1.26 g of 10% by mass oxalic acid aqueous solution was added dropwise into 20 mL of a mixed aqueous solution of 0.2 g of cadmium nitrate tetrahydrate, 0.18 g of zirconium oxynitrate hydrate, and 0.14 g of aluminum nitrate, and 10 mL of concentrated nitric acid was added dropwise thereto. The mixture was stirred at 800 rpm for 30 min at room temperature to obtain a white mixed solution. The solution was washed with deionized water and ethanol several times and dried at 110°C to obtain a white product. The obtained particles were crushed into particles less than 10 μm to obtain an organic-inorganic negative heat material. Embodiment 2

[0029] The preparation method of the flame retardant, high refractive, and drip resistant water-based polyurethane coating comprises the following steps: (1) 32 g of polytetramethylene ether diol (number average molecular weight: 2000 g / mol), 14.92 g of hexamethylene diisocyanate and 0.3 g of dibutyltin dilaurate were added into a 500 mL three-necked flask. Under nitrogen protection, the temperature was raised to 85 °C and the speed was 500 r / min for stirring and reaction for 2 h to obtain a polyurethane prepolymer. (2) Add 8.4 g of carbonizing agent to the polyurethane prepolymer and continue to react at 80°C for 2 h; cool to 60°C, add 0.89 g of 2,2-dihydroxymethylbutyric acid and 2.6 g of amino carbon nanotubes, and react at 65°C for 2 h; add 2.46 g of high refractive material and 1.21 g of 2,5-dimethylmercapto-1,4-dithiane, and react at 70°C for 2 h; cool to 40°C, add 2.1 g of triethylamine, and react for 1 h; cool to room temperature, add 80 mL of deionized water, and emulsify at a speed of 2000 r / min for 1.5 h; then add 13.15 g of ammonium polyphosphate (the degree of polymerization of ammonium polyphosphate is less than 20) solution dissolved in 10 g of water and 0.2-0.3 g of organic and inorganic negative heat material, and emulsify at a speed of 2000 r / min for 1 h. After the foam disappears, a flame retardant, high refractive, and drip-resistant water-based polyurethane coating is obtained.

[0030] Preparation method of flame retardant, high refractive, drip resistant water-based polyurethane coating, and preparation method of the carbon-forming agent: (1) Add 24.4 g of p-hydroxybenzaldehyde PHBA into a beaker, stir and dissolve it with 200 mL of ethanol, transfer it into a 500 mL three-necked flask, and heat it to 70 °C under nitrogen protection. The stirring speed is 500 r / min. Dilute 6.2 g of ethylenediamine with 50 mL of ethanol and add it dropwise to the p-hydroxybenzaldehyde solution for 50 min. Continue the reaction for 2.5 h. Cool it to room temperature and filter it to obtain a light yellow crude carbon-forming intermediate. Wash it with ethanol three times and dry it in a vacuum at 70 °C for 24 h to obtain a light yellow carbon-forming intermediate powder PHE. (2) Put 6.8 g of PHE described in step (1) in a beaker, add 1200 mL of ethanol as solvent, pour into a 500 mL three-necked flask, and heat to 80° C. under nitrogen protection. Add 3.2 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO4 and 1.2 g of N-vinylcarbazole. The speed is 300 r / min and the reaction is stirred for 6 h. Stop heating, cool to room temperature, filter and obtain a white crude carbonizing agent. Wash with ethanol 3 times and recrystallize with methanol several times to obtain a white carbonizing agent powder PHED. Dry in vacuum at 70° C. for 24 h to obtain the carbonizing agent.

[0031] The preparation method of amino carbon nanotubes is as follows: 0.7 g of carbon nanotubes were subjected to ultrasonic dispersion treatment for 3 h in the presence of 90 mL of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3: 1. After ultrasonication, the mixed solution was diluted with 100 mL of water, filtered with a vacuum pump, washed with deionized water until neutral, and dried at 105° C. overnight to obtain carboxylated carbon nanotubes; 3.25 g of phosphorus trichloride was dissolved in 10 mL of DMF solution, 0.205 g of carboxylated carbon nanotubes and 4.3 g of bis(2-ethylhexanoic acid)hydroxyaluminum were added, reacted at 60° C. for 60 min, then placed in a constant temperature oil bath at 80° C., 7.5 g of acrylamide was added, reacted for 48 h, washed with 10 mL of DMF and 30 mL of toluene in turn, filtered, and dried at 105° C. overnight in vacuum to obtain amino carbon nanotubes.

[0032] Preparation method of high refractive material: (1) Add 10.7 g of 2-carboxyethylphenylphosphorous acid into a 250 mL three-necked flask, add 60 mL of thionyl chloride, install a tail gas saturated sodium hydroxide solution treatment device, heat to 80 ° C, slowly pass nitrogen, stir and react for 3 hours, cool to room temperature, and remove thionyl chloride by rotary evaporation to obtain an oily liquid to obtain phosphorus impurities; (2) Under nitrogen protection, 57 g of 4-aminobenzenethiol was dissolved in 200 mL of 1,3-dimethyl-2-imidazolidinone, and 42 g of sodium carbonate and 150 mL of toluene were added and stirred. The temperature was raised to 140°C to collect the evaporated toluene, and the temperature was lowered to 120°C after the toluene was removed. Then, a mixed solution of 29 g of 2,5-dichlorothiophene and 60 mL of DMI was added to the reaction bottle and reacted for 8 h. Then, 22 g of the phosphorus dopant in step (1) was added and reacted at 110°C for 2 h. The obtained product was poured into 1 L of ice water and allowed to stand until the product solidified into a solid. The solid was collected by suction filtration and washed with a large amount of deionized water to finally obtain a pale yellow solid as a crude product. The crude product can be recrystallized from anhydrous ethanol to obtain a pure white needle-shaped solid, which is then mixed with 1.3 g of thiadiazole to obtain a high refractive material.

[0033] Preparation method of organic and inorganic negative heat materials: 1.26 g of 10% by mass oxalic acid aqueous solution was dripped dropwise into 20 mL of a mixed aqueous solution of 0.3 g of cadmium nitrate tetrahydrate, 0.22 g of zirconium oxynitrate hydrate, and 0.18 g of aluminum nitrate, and 15 mL of concentrated nitric acid was added dropwise thereto. The mixture was stirred at 1000 rpm for 60 min at room temperature to obtain a white mixed solution. The mixture was washed with deionized water and ethanol several times and dried at 140°C to obtain a white product. The obtained particles were crushed into particles less than 10 μm to obtain an organic-inorganic negative heat material. Embodiment 3

[0034] The preparation method of the flame retardant, high refractive, and drip resistant water-based polyurethane coating comprises the following steps: (1) 15.5 g of polypropylene glycol, 15.5 g of polytetramethylene ether glycol (the number average molecular weight of polypropylene glycol and polytetramethylene ether glycol are both 2000 g / mol), 7.46 g of isophorone diisocyanate, 7.46 g of hexamethylene diisocyanate and 0.25 g of dibutyltin dilaurate were added to a 500 mL three-necked flask. Under nitrogen protection, the temperature was raised to 80 ° C, the speed was 400 r / min, and the reaction was stirred for 1.5 h to obtain a polyurethane prepolymer; (2) Add 6.3 g of carbonizing agent to the polyurethane prepolymer and continue to react at 75 °C for 1.5 h; cool to 60 °C, add 0.81 g of 2,2-dihydroxymethylbutyric acid and 2.5 g of amino carbon nanotubes, and react at 60 °C for 1.5 h; add 2.05 g of high refractive material and 1.14 g of 2,5-dimethylmercapto-1,4-dithiane, and react at 65 °C for 1.5 h; cool to 40 °C, add 2.1 g of triethylamine and react for 0.75 h; cool to room temperature, add 62 mL of deionized water, and heat at 2000 °C. R / min speed for 1 hour of high-speed shear emulsification, then add 13.15g of ammonium polyphosphate (the degree of polymerization of ammonium polyphosphate is less than 20) solution dissolved in 10g of water and 0.25g of organic and inorganic negative heat material, and high-speed shear emulsification at 1500r / min speed for 0.75h. When the foam disappears, a flame-retardant, high-refractive, drip-resistant water-based polyurethane coating is obtained.

[0035] Preparation method of flame retardant, high refractive, drip resistant water-based polyurethane coating, and preparation method of the carbon-forming agent: (1) Add 24.4 g of p-hydroxybenzaldehyde PHBA into a beaker, stir and dissolve it with 175 mL of ethanol, transfer it into a 500 mL three-necked flask, and heat it to 65°C under nitrogen protection. The stirring speed is 400 r / min. Dilute 6.1 g of ethylenediamine with 50 mL of ethanol and add it dropwise to the p-hydroxybenzaldehyde solution for 40 min. Continue the reaction for 2 h. Cool it to room temperature, filter it, and obtain a light yellow crude carbon-forming intermediate. Wash it with ethanol twice, and vacuum dry it at 65°C for 18 h to obtain a light yellow carbon-forming intermediate powder PHE. (2) Put 26.8 g of PHE described in step (1) in a beaker, add 175 mL of ethanol as solvent, pour into a 500 mL three-necked flask, and heat to 75°C under nitrogen protection. Then add 2.6 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO4 and 0.95 g of N-vinylcarbazole. Stir at a speed of 250 r / min and react for 4.5 h. Stop heating, cool to room temperature, filter and obtain a white crude carbonizing agent. Wash with ethanol twice and recrystallize with methanol several times to obtain a white carbonizing agent powder PHED. Dry in vacuum at 65°C for 24 h to obtain the carbonizing agent.

[0036] The preparation method of amino carbon nanotubes is as follows: 0.65 g of carbon nanotubes were subjected to ultrasonic dispersion treatment for 2.5 h in concentrated sulfuric acid and concentrated nitric acid 85 mL in a volume ratio of 3: 1. After ultrasonication, the mixed solution was diluted with 90 mL of water, filtered with a vacuum pump, washed with deionized water until neutral, and dried at 105° C. overnight to obtain carboxylated carbon nanotubes; 3.12 g of phosphorus trichloride was dissolved in 10 mL of DMF solution, 0.205 g of carboxylated carbon nanotubes and 4.3 g of bis(2-ethylhexanoic acid)hydroxyaluminum were added, and the mixture was reacted at 55° C. for 45 min, then placed in a 75° C. constant temperature oil bath, 7.35 g of acrylamide was added, and the mixture was reacted for 36 h, and then washed with 10 mL of DMF and 30 mL of toluene in turn, filtered, and dried at 105° C. overnight in vacuum to obtain amino carbon nanotubes.

[0037] Preparation method of high refractive material: (1) Add 10.7 g of 2-carboxyethylphenylphosphorous acid into a 250 mL three-necked flask, add 55 mL of thionyl chloride, install a tail gas saturated sodium hydroxide solution treatment device, heat to 75 ° C, slowly pass nitrogen, stir and react for 2.5 hours, cool to room temperature, and remove thionyl chloride by rotary evaporation to obtain an oily liquid to obtain phosphorus impurities; (2) Under nitrogen protection, 55.5 g of 4-aminobenzenethiol was dissolved in 200 mL of 1,3-dimethyl-2-imidazolidinone, and 41 g of sodium carbonate and 150 mL of toluene were added and stirred. The temperature was raised to 130° C. to collect the evaporated toluene, and the temperature was lowered to 115° C. after the toluene was removed. Then, a mixed solution of 29 g of 2,5-dichlorothiophene and 55 mL of DMI was added to the reaction bottle and reacted for 7 h. Then, 21.7 g of the phosphorus impurity in step (1) was added and reacted at 100° C. for 1.5 h. The obtained product was poured into 1 L of ice water and allowed to stand until the product solidified into a solid. The solid was collected by suction filtration and washed with a large amount of deionized water to finally obtain a pale yellow solid as a crude product. The crude product can be recrystallized from anhydrous ethanol to obtain a pure white needle-shaped solid, which is mixed with 1.3 g of thiadiazole to obtain a high refractive material.

[0038] Preparation method of organic and inorganic negative heat materials: 1.26 g of 10% by mass oxalic acid aqueous solution was added dropwise into 20 mL of a mixed aqueous solution of 0.25 g of cadmium nitrate tetrahydrate, 0.2 g of zirconium oxynitrate hydrate, and 0.16 g of aluminum nitrate, and 12.5 mL of concentrated nitric acid was added dropwise thereto. The mixture was stirred at 900 rpm for 45 min at room temperature to obtain a white mixed solution. The mixture was washed with deionized water and ethanol several times and dried at 120°C to obtain a white product. The obtained particles were crushed into particles less than 10 μm to obtain an organic-inorganic negative heat material.

[0039] The prepared polyurethane coating was poured into a polytetrafluoroethylene mold with a thickness of 3 mm, and the droplet test, cone calorimetry and other tests were performed.

[0040] Droplet test (1) Sample preparation: Place the prepared polyurethane film in a constant temperature and humidity chamber set at 23°C ± 0.5°C and 50% ± 5% humidity for 48 h. Then take out the film and cut it into samples of 110 cm × 10 cm × 3 mm. Prepare 2 sets of samples, with 5 samples in each set.

[0041] (2) Parameters: Clamp about 5mm from the top so that the sample is vertically downward, place a rosin board at the bottom of the sample, and pad about 0.3g of absorbent cotton on the board, evenly placed on the board. Adjust the gas flow rate to 105±5 mL / min, so that the flame height reaches 20±1mm, and set the combustion time to 10s.

[0042] (3) Flame recording: After setting the parameters, start the flame ignition. After the 10s ignition, press the afterflame time start button. When the sample combustion is finished and only sparks are left, press the afterflame combustion end button and enter the afterburning time. When the flame is completely extinguished, press the afterburning time end button and record the burning afterflame time and afterburning time.

[0043] (4) Molten droplet observation: During the combustion process, pay attention to whether the combustion produces molten droplets, and whether the molten droplets dripping onto the cotton wool below will cause secondary combustion. Record the observation results.

[0044] The ASTM E1354-1990 (2004 standard) was used, and the cone calorimeter 2000 of the British FTT company was used for analysis and determination. The sample was 10cm×10cm, the thickness was 3mm, and the thermal radiation power was 12kW / m 2 , determine the maximum heat release rate pkHHR kW / m 2 ,THR total heat release MJ / m², pSPR smoke generation rate reaches peak value m 2 / s and maximum total smoke release (TSR) m 2 / m 2 .

[0045] Yellowing resistance is measured by observing the color change under ultraviolet light under simulated sunlight for 48 hours. To determine the yellowing resistance, the HZ-3017 bulb-type yellowing resistance instrument was used for testing.

[0046] The transmittance of polymer films was tested using a UV-7504 ultraviolet-visible spectrophotometer.

[0047] The refractive index of the emulsion was tested using an Abbe refractometer.

[0048] The shrinkage rate of the film is the area of ​​the polyurethane emulsion formed into a film at 80°C and the area cooled to room temperature. The percentage of the difference between the area at room temperature and the area formed into a film at 80°C to the area formed into a film at 80°C is the shrinkage rate.

[0049] Table 1 Film-forming properties of flame-retardant, high-refractive and drip-resistant water-based polyurethane coatings Embodiment 1 Embodiment 2 Embodiment 3 Comparative Example Burning droplet phenomenon No melting and no dripping No melting and no dripping No melting and no dripping No melting and no dripping HkDJ 38.45 38.87 39.01 41.26 THR 115.13 116.98 116.56 128.21 pSPR smoke generation rate 0.193 0.196 0.186 0.205 TSR 835.2 823.8 828.6 998.3 Yellowing resistance (grade) 4.0 4.0 4.0 4.0 Oxygen index (%) 33.6 33.2 33.4 28.6 Refractive Index 1.83 1.88 1.81 1.31 Light transmittance(%) 95.6 95.9 95.4 84.3 Film shrinkage (%) 2.4 1.7 2.1 4.7 As can be seen from Table 1, the flame retardancy (burning droplet phenomenon), pkHHR, and THR of the polyurethane film of the present invention are significantly improved compared with the comparative example CN118813133B (Example 1); due to the component effect of the dense carbon layer in the polyurethane segment of the present invention, the obtained polyurethane does not produce droplets and drippings when burned, and its pkHHR and THR are lower than those of the comparative example, and the peak value of the pSPR smoke generation rate and the maximum total smoke release of the combustion are both reduced relative to the comparative example. Due to the synergistic effect of the hydroxyl group, dichlorothionyl and 2,5-dichlorothiophene in 2-carboxyethylphenylphosphorous acid, the yellowing resistance, refractive index and light transmittance of the obtained polyurethane film are greatly improved, and the synergistic effect of the amino nanotubes, APP and the carbon-forming agent makes the oxygen index of the obtained polyurethane film exceed 32%, overcoming the deficiency that a single type of flame retardant component is difficult to increase to 32% (non-combustible).

[0050] Taking the second embodiment of the present invention as an example, a comparative test is performed.

[0051] Table 2 Film-forming properties of flame-retardant, high-refractive and drip-resistant water-based polyurethane coatings Embodiment 2 Element Burning droplet phenomenon Large amount of molten droplets Carbon nanotubes without amino group HkDJ 53.67 Carbon nanotubes without amino group THR 153.26 Carbon nanotubes without amino group pSPR smoke generation rate 0.387 Carbon nanotubes without amino group TSR 1035.86 Carbon nanotubes without amino group Oxygen index (%) 32.2 Carbon nanotubes without amino group Burning droplet phenomenon There are molten drops but no dripping Add amino carbon nanotubes, without bis(2-ethylhexanoate)hydroxyaluminum HkDJ 43.35 Add amino carbon nanotubes, without bis(2-ethylhexanoate)hydroxyaluminum THR 143.61 Add amino carbon nanotubes, without bis(2-ethylhexanoate)hydroxyaluminum pSPR smoke generation rate 0.276 Add amino carbon nanotubes, without bis(2-ethylhexanoate)hydroxyaluminum TSR 931.57 Add amino carbon nanotubes, without bis(2-ethylhexanoate)hydroxyaluminum Oxygen index (%) 32.8 Add amino carbon nanotubes, without bis(2-ethylhexanoate)hydroxyaluminum Burning droplet phenomenon No melting and no dripping Add amino carbon nanotubes, no acrylamide HkDJ 41.16 Add amino carbon nanotubes, no acrylamide THR 123.24 Add amino carbon nanotubes, no acrylamide pSPR smoke generation rate 0.213 Add amino carbon nanotubes, no acrylamide TSR 846.21 Add amino carbon nanotubes, no acrylamide Oxygen index (%) 33.0 Add amino carbon nanotubes, no acrylamide Oxygen index (%) 28.3 No carbon added Burning droplet phenomenon There are molten drops and drips No carbon added Oxygen index (%) 28.6 Without APP (ammonium polyphosphate) Burning droplet phenomenon No drip No drip No APP added As can be seen from Table 2, bis(2-ethylhexanoic acid) hydroxyaluminum, acrylamide and amino carbon nanotubes can all improve the flame retardancy of polyurethane. Among them, APP improves the oxygen index of polyurethane, but it is accompanied by the generation of burning droplets. The ideal polyurethane flame retardant is to improve the oxygen index without droplets and dripping. The more ideal flame retardant method is to burn the droplets to take away part of the heat to achieve flame retardancy; the addition of inorganic flame retardant APP makes the resulting polyurethane burn, and the droplets and drips take away part of the heat to achieve the flame retardant effect, which is a more ideal flame retardant method. It cooperates with amino carbon nanotubes, carbon-forming agents and APP to improve flame retardancy while no droplets are generated, which is an ideal flame retardant method.

[0052] Table 3 Film-forming properties of flame-retardant, high-refractive and drip-resistant water-based polyurethane coatings Embodiment 2 Ingredients Yellowing resistance (grade) 3.0 No high refractive material added Refractive Index 1.35 No high refractive material added Light transmittance(%) 85.6 No high refractive material added Yellowing resistance (grade) 3.5 Add high refractive material, but not 2-carboxyethylphenylphosphite Refractive Index 1.62 Add high refractive material, but not 2-carboxyethylphenylphosphite Light transmittance(%) 90.4 Add high refractive material, but not 2-carboxyethylphenylphosphite Yellowing resistance (grade) 3.5 Add high refractive material, but not 2,5-dichlorothiophene Refractive Index 1.58 Add high refractive material, but not 2,5-dichlorothiophene Light transmittance(%) 91.3 Add high refractive material, but not 2,5-dichlorothiophene Yellowing resistance (grade) 3.5 Add high refractive material, but not thiadiazole Refractive Index 1.62 Add high refractive material, but not thiadiazole Light transmittance(%) 90.5 Add high refractive material, but not thiadiazole Yellowing resistance (grade) 3.5 Without 2,5-dimethylmercapto-1,4-dithiane Refractive Index 1.75 Without 2,5-dimethylmercapto-1,4-dithiane Light transmittance(%) 93.3 Without 2,5-dimethylmercapto-1,4-dithiane Film shrinkage (%) 4.1 Without N-vinyl carbazole Refractive Index 1.86 Without N-vinyl carbazole Film shrinkage (%) 3.2 No organic or inorganic negative heat material added As shown in Table 3, 4-aminothiophenol is the core component of the high-refractive material. If it is not applied, the main material constituting the high-refractive material does not exist, and the yellowing resistance, refractive index and light transmittance of the obtained polyurethane are reduced; it can be found from Table 3 that the high-refractive material, 2-carboxyethylphenylphosphite, 2,5-dichlorothiophene and 2,5-dimethylmercapto-1,4-dithiane can all increase the refractive index of the polyurethane; N-vinyl carbazole has a nitrogen-fused ring structure, and the polyurethane treated with it shows less shrinkage after curing and good heat resistance; in addition, the organic and inorganic negative thermal materials have negative expansion at high temperature and recovery at room temperature, so the shrinkage rate of the modified polyurethane film decreases.

Claims

1. A method for preparing a flame retardant, high refractive, and drip resistant water-based polyurethane coating, characterized in that: Prepare according to the following steps: (1) Add 30-32 g of diol, 14.92 g of isocyanate and 0.2-0.3 g of dibutyltin dilaurate into a 500 mL three-necked flask. Under nitrogen protection, heat to 70-85 °C, rotate at 300-500 r / min, and stir for 1-2 h to obtain a polyurethane prepolymer. (2) Add 4.2-8.4 g of carbonizing agent to the polyurethane prepolymer, and continue to react at 70-80 °C for 1-2 h; cool to 60 °C, add 0.73-0.89 g of 2,2-dihydroxymethylbutyric acid and 2.4-2.6 g of amino carbon nanotubes, and react at 60-65 °C for 1-2 h; add 1.64-2.46 g of high refractive material and 1.06-1.21 g of 2,5-dimethylmercapto-1,4-dithiane, and react at 65-70 °C for 1-2 h; cool to 40 °C, add 2.1 g of triethylamine, and react for 0.5-1 h; cool to room temperature, add 50-80 mL of deionized water, and heat at 2000 °C. r / min, high-speed shear emulsification is carried out for 0.5~1.5h, and then 13.15g of ammonium polyphosphate solution dissolved in 10g of water and 0.2~0.3g of organic and inorganic negative heat materials are added. At a speed of 1000~2000 r / min, high-speed shear emulsification is carried out for 0.5~1h. When the foam disappears, a flame-retardant, high-refractive, and drip-resistant water-based polyurethane coating is obtained.

2. The method for preparing the flame-retardant, high-refractive, and drip-resistant water-based polyurethane coating according to claim 1, characterized in that: The diol is any one of polypropylene glycol and polytetramethylene glycol or a mixture of the two in any ratio.

3. The method for preparing the flame-retardant, high-refractive, and drip-resistant water-based polyurethane coating according to claim 1, characterized in that: The isocyanate is any one of isophorone diisocyanate and hexamethylene diisocyanate or a mixture of the two in any ratio.

4. The method for preparing the flame-retardant, high-refractive, and drip-resistant water-based polyurethane coating according to claim 1, characterized in that: The number average molecular weights of the polypropylene glycol and polytetramethylene glycol are both 2000 g / mol.

5. The method for preparing the flame-retardant, high-refractive, and drip-resistant water-based polyurethane coating according to claim 1, characterized in that: The preparation method of the carbon-forming agent: (1) Add 24.4 g of p-hydroxybenzaldehyde PHBA into a beaker, stir and dissolve it with 150-200 mL of ethanol, transfer it into a 500 mL three-necked flask, and heat it to 60-70 °C under nitrogen protection. The stirring speed is 300-500 r / min. Dilute 6-6.2 g of ethylenediamine with 50 mL of ethanol and add it dropwise to the p-hydroxybenzaldehyde solution for 30-50 min. Continue the reaction for 2-2.5 h. Cool it to room temperature, wash it with ethanol 2-3 times, and vacuum dry it at 60-70 °C for 12-24 h to obtain a light yellow carbon-forming intermediate powder PHE. (2) Put 26.8 g of PHE described in step (1) in a beaker, add 150-200 mL of ethanol as a solvent, pour into a 500 mL three-necked flask, and heat to 70-80° C. under nitrogen protection. Add 2-43.2 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO4 and 0.7-1.2 g of N-vinylcarbazole. Stir at a speed of 200-300 r / min and react for 3-6 h. Stop heating, cool to room temperature, and filter to obtain a white crude carbon-forming agent. Wash with ethanol 2-3 times, recrystallize with methanol several times, and dry in a vacuum at 60-70° C. for 24 h to obtain the carbon-forming agent.

6. The method for preparing the flame-retardant, high-refractive, and drip-resistant water-based polyurethane coating according to claim 1, characterized in that: The amino carbon nanotube preparation method is as follows: 0.6-0.7 g of carbon nanotubes were subjected to ultrasonic dispersion treatment for 2-3 h in the presence of 80-90 mL of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:

1. After ultrasonication, the mixed solution was diluted with 80-100 mL of water, the acid solution was filtered with a vacuum pump, washed with deionized water until neutral, and dried at 105°C overnight to obtain carboxylated carbon nanotubes. 3.00-3.25 g of phosphorus trichloride was dissolved in DMF solution, 0.205 g of carboxylated carbon nanotubes and 4.3 g of bis(2-ethylhexanoic acid) hydroxyaluminum were added, and the mixture was reacted at 50-60°C for 30-60 min, then placed in a constant temperature oil bath at 70-80°C, 7.2-7.5 g of acrylamide was added and reacted for 24-48 h, and the mixture was washed with 10 mL of DMF and 30 mL of toluene in sequence, filtered, and dried at 105°C in vacuum overnight to obtain amino carbon nanotubes.

7. The method for preparing the flame-retardant, high-refractive, and drip-resistant water-based polyurethane coating according to claim 1, characterized in that: The preparation method of the high refractive material: (1) Add 10.7 g of 2-carboxyethylphenylphosphorous acid into a 250 mL three-necked flask, add 50-60 mL of thionyl chloride, install a tail gas saturated sodium hydroxide solution treatment device, heat to 70-80 ° C, slowly pass nitrogen, stir and react for 2-3 hours, cool to room temperature, and remove thionyl chloride by rotary evaporation to obtain an oily liquid to obtain phosphorus impurities; (2) Under nitrogen protection, 54-57 g of 4-aminothiophenol was dissolved in 200 mL of 1,3-dimethyl-2-imidazolidinone, and 40-42 g of sodium carbonate and 150 mL of toluene were added and stirred. The temperature was raised to 120-140°C to collect the evaporated toluene. After the toluene was removed, the temperature was lowered to 110-120°C. Then, a mixed solution of 29 g of 2,5-dichlorothiophene and 50-60 mL of 1,3-dimethyl-2-imidazolidinone was added to the reaction mixture. The mixture was placed in a bottle and reacted for 6 to 8 hours. Then 21.5 to 22 g of the phosphorus dopant from step (1) was added and reacted at 90 to 110°C for 1 to 2 hours. The obtained product was poured into 1 L of ice water and allowed to stand until the product solidified into a solid. The solid was collected by filtration and washed with a large amount of deionized water to finally obtain a pale yellow solid as a crude product. The crude product can be recrystallized from anhydrous ethanol to obtain a pure white needle-shaped solid, which is then mixed with 1.3 g of thiadiazole to obtain a high refractive material.

8. The method for preparing the flame-retardant, high-refractive, and drip-resistant water-based polyurethane coating according to claim 1, characterized in that: The degree of polymerization of the ammonium polyphosphate is less than 20.

9. The method for preparing the flame-retardant, high-refractive, and drip-resistant water-based polyurethane coating according to claim 1, characterized in that: Preparation method of organic and inorganic negative heat materials: 1.26 g of 10% by mass oxalic acid aqueous solution was added dropwise into 20 mL of a mixed aqueous solution of 0.2-0.3 g of cadmium nitrate tetrahydrate, 0.18-0.22 g of zirconium oxynitrate hydrate, and 0.14-0.18 g of aluminum nitrate, and 10-15 mL of concentrated nitric acid was added dropwise thereto. The mixture was stirred at room temperature at a speed of 800-1000 rpm for 30-60 min to obtain a white mixed solution. The mixture was washed with deionized water and ethanol several times, and dried at 110-140° C. to obtain a white product. The obtained particles were crushed into particles less than 10 μm to obtain an organic-inorganic negative heat material.

Citation Information

Patent Citations

  • Naked-eye 3D display screen material and preparation method thereof

    CN111303478A

  • Preparation and application methods of self-healing flame-retardant, drip-resistant, and abrasion-resistant polyurethane coatings

    CN113956777B

  • Preparation method of graphene-type flame-retardant, light-resistant and wear-resistant water-based polyurethane coating

    CN118813133B

  • Preparation method of flame-retardant, washable and melt-drop-resistant polyurethane coating

    CN119320596A

  • Preparation method of carbon nano tube modified conductive flame-retardant polyurethane paint and adhesive

    CN104449323A

Cited By

  • Polyurethane finish paint and preparation method thereof

    CN120519079A

  • Preparation method of heat-resistant, high-adhesion and high-conductivity acrylate resin adhesive

    CN121975463A